2021
DOI: 10.1111/bjop.12482
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting off‐line segmentation decisions with on‐line word segmentation during reading

Abstract: In two experiments, we investigated the correspondences between off‐line word segmentation and on‐line segmentation processing during Chinese reading. In Experiment 1, participants were asked to read sentences which contained critical four‐character strings, and then, they were required to segment the same sentences into words in a later off‐line word segmentation task. For each item, participants were split into 1‐word segmenters (who segmented four‐character strings as a single word) and 2‐word segmenters (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…It is very likely that the requirement to process three compared with two constituent characters led to the delayed and more substantive effects that were observed in Experiment 2 relative to Experiment 1. This suggestion aligns with arguments put forward by He et al (2021) and Zang et al (2018) who each showed reading time costs associated with processing an increased number of linguistic constituents in character strings that were otherwise comparable. Nonetheless, it is certainly the case that further research is required to better understand the time course of reading time effects (i.e., how they emerge, their extent, and when they terminate) over linguistic constituents of different types that may also differ in length during Chinese reading.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It is very likely that the requirement to process three compared with two constituent characters led to the delayed and more substantive effects that were observed in Experiment 2 relative to Experiment 1. This suggestion aligns with arguments put forward by He et al (2021) and Zang et al (2018) who each showed reading time costs associated with processing an increased number of linguistic constituents in character strings that were otherwise comparable. Nonetheless, it is certainly the case that further research is required to better understand the time course of reading time effects (i.e., how they emerge, their extent, and when they terminate) over linguistic constituents of different types that may also differ in length during Chinese reading.…”
Section: Discussionsupporting
confidence: 88%
“…There are also no visual or lexical indicators to mark each word’s syntactic property, and word order is relatively free. Furthermore, there is sometimes ambiguity concerning the concept of a word in Chinese, and it is not straightforward for readers to discriminate words from other linguistic units such as phrases (e.g., Bai et al, 2008; He et al, 2021; Hoosain, 1992; Liu et al, 2013). Note that despite these characteristics, there is considerable evidence demonstrating that words in Chinese are psychologically real and play an important and fundamental role during reading (e.g., Bai et al, 2008; Li et al, 2013, 2014; see also Li et al, 2015; Li & Pollatsek, 2020; Zang et al, 2011 for reviews).…”
Section: Open Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, up to 90 % of Chinese characters are comprised of semantic (and phonetic) radicals, conveying meaning information about the characters (Hoosain, 1991;Zang, Liversedge, Bai, & Yan, 2011). Third, word boundary ambiguity is prevalent in Chinese (He et al, 2021), which may require readers to allocate more attention to the parafoveal characters for successful word segmentation and optimised saccadic targeting. All these characteristics may lead to aspects of semantic meaning being accessed efficiently from the parafovea (e.g., Yan, Richter, Shu, & Kliegl, 2009), which in turn might influence processing of the foveal word and result in possible lexical PoF effects for Chinese readers.…”
mentioning
confidence: 99%